MEDICINAL PLANT DIVERSITY IN THE TESSO NILO NATIONAL PARK, RIAU, SUMATRA, INDONESIA* - Susiarti, Siti; Purwanto, Yohanes; Walujo, Eko Baroto (Research Center for Biology, 2009)
SUSIARTI, S., PURWANTO, Y. & WALUJO, E.B. 2009. Medicinal plant diversity in the Tesso Nilo National Park, Riau, Sumatra, Indonesia. ReinwardtiaÂ Â 12(5): 383â390- A study of traditional knowledge on plant uses especially medicinal plants of the local community, was conducted in 2003 at the Situgal Village and its surrounding area in the Tesso Nilo National Park at the Logas Tanah Darat District, Riau Province, Sumatra, Indonesia. Research methods included open-ended discussion and direct observation. To better assess the extractive activities and the utilization of the plant diversity by the local people, an index of cultural significance (ICS) analysis was employed. Research results showed that local people in Situgal still use a large number of plants for medicinal purposes and rely on ethnobotanical knowledge in their daily life. We recorded 86 species belonging to 78 genera and 46 families of plants having ethnobotanical values. Eighty-two species are used for medicinal purposes and the remaining 4 species for fish poisons. Those species can be used to cure approximately 38 types of illness. The ICS analysis for the potential value of each species showed thatÂ Â âpatalo bumiâÂ (Eurycoma longifolia) is the most important species and well utilized by local community in the Tesso Nilo NP area.